A comparison of β-casein complexes and micelles as vehicles for trans-/cis-resveratrol. (15th November 2020) - Cheng, Hao; Dong, Huanhuan; Wusigale; Liang, Li
Highlights: β-Casein can bind trans - and/or cis -resveratrol to form β-casein-ligand complexes. Both trans - and cis -resveratrol could be entrapped by β-casein micelles. β-Casein micelles delayed isomerization more effectively than protein complexes. β-Casein complexes showed better protective effect for resveratrol than micelles. Abstract: Bovine β-casein is an amphiphilic protein that exists as a monomer and self-organizes into micelles in aqueous solution. The protein has been used as natural vehicles for bioactives. Trans- resveratrol has received significant attention due to its vast health benefits and conversion to cis -isomer during processing and storage. However, cis -isomer has not yet gained as much attention as that of trans -isomer. In this study, the interaction of β-casein with trans - and cis -resveratrol was characterized. Trans -resveratrol exhibited a higher affinity for β-casein than cis -isomer, and β-casein could bind two isomers simultaneously to form protein-diligand complexes. Both trans - and cis -isomers could be encapsulated into β-casein micelles with encapsulation efficiencies of ~69% and ~57%, respectively. The β-casein micelles could delay photo-isomerization of trans -isomer to cis -isomer, while β-casein-ligand complex showed a better protective effect for both isomers during storage than β-casein micelles. These results might be useful for the development of protein-based carriers for the polyphenols.